ALLERGY SPREAD AMONG SCHOOLCHILDREN OF ASTRAKHAN - D.A. Bezrukova; L.S. Namazova; A.A. Dzhumagaziev; O.A. Shelkova (Union of pediatricians of Russia, 2007)
The article presents the results of the questionnaire survey carried on among schoolchildren of astrakhan' in compliance with the isaac (international study of asthma and allergy in childhood) program protocol - an international research of bronchial asthma and allergy among children on the basis of the standardized methods recommended and approved by WHO.Key words: schoolchildren, bronchial asthma, allergic rhinitis, atopic dermatitis